2015
DOI: 10.1117/12.2177465
|View full text |Cite
|
Sign up to set email alerts
|

On a simulation study of cyber attacks on vehicle-to-infrastructure communication (V2I) in Intelligent Transportation System (ITS)

Abstract: An intelligent transportation system (ITS) is one typical cyber-physical system (CPS) that aims to provide efficient, effective, reliable, and safe driving experiences with minimal congestion and effective traffic flow management. In order to achieve these goals, various ITS technologies need to work synergistically. Nonetheless, ITS's reliance on wireless connectivity makes it vulnerable to cyber threats. Thus, it is critical to understand the impact of cyber threats on ITS. In this paper, using real-world tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…There are mainly two sources of attack, i.e., the vehicle and the RSU. Attacks that can be launched by the vehicle are similar to V2VC attacks and have been extensively explored [9]- [11]. In this section, we mainly focus on detection mechanisms for attacks launched by a compromised RSU.…”
Section: A Related Workmentioning
confidence: 99%
“…There are mainly two sources of attack, i.e., the vehicle and the RSU. Attacks that can be launched by the vehicle are similar to V2VC attacks and have been extensively explored [9]- [11]. In this section, we mainly focus on detection mechanisms for attacks launched by a compromised RSU.…”
Section: A Related Workmentioning
confidence: 99%
“…Two studies were found that quantified the impact of cyberattacks against CAVs in terms of transportation MOEs. Ekedebe et al (2015) studied the effect of a jamming DoS attack on a transportation network following a crash and the subsequent traffic backup. Similarly, Garip et al (2015) demonstrated how a vehicular botnet could impact roadway traffic operations and travel times.…”
Section: Cybersecurity In Transportation Engineeringmentioning
confidence: 99%
“…However, neither presented detailed, quantifiable impacts on safety. Ekedebe et al (2015) set up a simulation where upstream traffic was slowed/stopped due to a crash. A jamming DoS attack was implemented on downstream vehicles, ranging from 0 to 100% communication jam.…”
Section: Cybersecurity In Transportation Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…DDoS attacks on V2I networks are likely to disrupt transportation in a large region, especially if the infrastructure provides critical information to control traffic flows. Ekedebe et al (2015) [176] experimented with DoS attacks on V2I network by using a simulated environment and showed that DoS attacks can prevent all messages from being sent to vehicles in the network. V2V networks are also possible targets for DoS and DDoS attacks because they have limited connection bandwidth.…”
Section: H Attacks On Communication Mechanismsmentioning
confidence: 99%